How does CSR of food company affect customer loyalty in the context of COVID-19: A moderated mediation model - N. Zhang (International Journal of Corporate Social Responsibility (JCSR), 2022)
Because of COVID-19 in the world, enterprises and consumers pay more and more attention to environmental protection, food safety and health issues. The purpose of this paper is to take China's food company as an example to study the impact of CSR on customer loyalty, mediating effects of company image and customer satisfaction, and moderating effects of COVID-19. The result shows that during COVID-19, company image and customer satisfaction have significant mediating effects, and COVID-19 positively moderate the impact of CSR on customer satisfaction.
Keywords: 650; CSR; Customer loyalty; COVID-19; Moderating effects